2020
DOI: 10.1007/s00134-020-06010-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome-attributable mortality in critically ill patients with sepsis

Abstract: Previous studies assessing impact of acute respiratory distress syndrome (ARDS) on mortality have shown conflicting results. We sought to assess the independent association of ARDS with in-hospital mortality among intensive care unit (ICU) patients with sepsis. Methods: We studied two prospective sepsis cohorts drawn from the Early Assessment of Renal and Lung Injury (EARLI; n = 474) and Validating Acute Lung Injury markers for Diagnosis (VALID; n = 337) cohorts. ARDS was defined by Berlin criteria. We used lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 38 publications
7
77
2
2
Order By: Relevance
“…Here, we con rmed that those with increased SOFA, qSOFA, APACHE II or SIRS score had higher death risk of COVID-19. Additionally, the AUC values predicting death risk of COVID-19 using SOFA, qSOFA, APACHE II or SIRS score attained 0.697, 0.610, 0.826 and 0.749, respectively, consistent with previous reports revealing that these scores are useful predictors of ICU mortality [18][19][20]. Strikingly, it was reported that SOFA and qSOFA scores had greater capacities predicting death in ICU cohort, compared to APACHE II or SIRS score [20,21].…”
Section: Discussionsupporting
confidence: 87%
“…Here, we con rmed that those with increased SOFA, qSOFA, APACHE II or SIRS score had higher death risk of COVID-19. Additionally, the AUC values predicting death risk of COVID-19 using SOFA, qSOFA, APACHE II or SIRS score attained 0.697, 0.610, 0.826 and 0.749, respectively, consistent with previous reports revealing that these scores are useful predictors of ICU mortality [18][19][20]. Strikingly, it was reported that SOFA and qSOFA scores had greater capacities predicting death in ICU cohort, compared to APACHE II or SIRS score [20,21].…”
Section: Discussionsupporting
confidence: 87%
“…H2A, H2B, H3 and H4 known as core histones and H1 and H5 as designated as linker histones remain inert in the nucleus, but once released into extracellular space, they act as damage-associated molecular patters (DAMPs) and may exert profound cytotoxic effects 2,3 . Acute respiratory distress syndrome (ARDS) and severe sepsis still remain the most common cause of mortality in critically ill patients 4 . Recent studies have linked histones to the proposed pathogenesis of these disorders by associating the levels of circulating histones with severity of illness 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of patients in which liver fibrosis indexes could not be calculated was similar to that in the rest of the cohort (Supplementary table 1). [20,21] and has been associated with poorer outcomes in chronic liver disease [22]; furthermore, the APACHE II is a widely validated score for the assessment of prognosis in critically ill patients, including those with acute respiratory failure and ARDS as a primary cause of admission [23,24]. Our findings confirm a recent report indicating that the severity of COVID-19 was significantly less intense in patients with a low risk of the fibrosis FIB-4 category as compared with those with intermediate or high fibrosis categories [8].…”
Section: Baseline Factors Related To Survivalmentioning
confidence: 99%